Fright night on Channel 9 Saturday night horror films on New York's WOR-TV, 1973-1987 - Arena, James, 1960- (McFarland & Co., 2012)
"This affectionate tribute to Fright Night's glory days includes a complete listing of all films shown on the series, as well as discussion of WOR-TV's other horror movie programs from the 1970s and 1980s. Also featured are interviews with the major surviving players, including series creator Lawrence P. Casey, who were responsible for the Fright Night experience"--Provided by publisher.